Intermolecular photoreactions and selectivity studies in confined space of cation-exchanged y zeolites - Yeoh, Kar Kheng (2005)
Photochemistry in organized assemblies has attracted considerable attention because of their potential use in controlling photophysical and photochemical behaviour of organic molecules in a confined space. Conversion of a starting material to product in a photoreaction involves selectivity by the reaction cavity to the specified product. For solid and rigid media like zeolite, the size of the reaction cavity plays an important role in products selectivity. The surface of NaY zeolite was first studied with paramagnetic probe using Electron Spin Resonance spectroscopy (ESR). Two favourable active sites were identified. The study of a confine space reaction was first studied in the photosensitization of triethylamine by acetophenone in NaY zeolite. ESR result showed that radical cation of amine dimer was formed inside zeolite resulted from the confinement effect of the zeolite Y supercage. Ultraviolet (UV) irradiation of acetophenone in toluene solution results in photochemical hydrogen abstraction and yielded a mixture of both symmetric (1,2-diphenylethane and 1,2-diphenylethyl alcohol) and asymmetric (1,2-diphenylpinacol) coupling products. These were identified and characterized by gas chromatography-mass spectrometry (GC-MS) and nuclear magnetic resonance (NMR). With the introduction of NaY zeolite, high yield of asymmetric product, 1,2-diphenylpinacol was observed. It further proved the confinement effect played by the zeolite produced a drastic change in product selectivity compared to homogenous reaction. Photodimerization of 2-cyclohexenone in various cation-exchanged Y zeolites were also studied in solid state and zeolite-solvent slurries. Both the reactions showed a great reversal of head-to-tail (HT) cyclohexenone dimer, to head-to-head (HH) cyclohexenone dimer with increasing pattern from LiY to CsY zeolite. The study of regioselectivity in the photocycloaddition of 2-cyclohexenone to vinyl acetate was also carried out in zeolite slurries, in which the result showed a drastically change of product yield compared to the homogeneous reaction. However, the cationexchanged zeolites failed to control the selectivity. This is explained by the passive cavity effect of zeolite.